DEVELOPMENT OF TOURISM AND THE HOSPITALITY SECTOR IN THE CONTEXT OF PROTECTING HISTORICAL HERITAGE: BALANCING BUSINESS INTERESTS AND COMMUNITY CULTURAL IDENTITY (Development Service Industry Management, 2025)
The development of tourism and the hospitality sector in the historical locations of Ukrainian cities requires balancing the economic interests of businesses with the protection of cultural heritage within local communities. Particular attention should be paid to businesses operating under the franchise model: the franchisors’ requirements for certain brand standards (logos, colors, typical signboard formats) are often mandatory contract conditions and directly influence the appearance of façades. This creates certain contradictions between the franchisor’s requirements and local design codes aimed at protecting historical and cultural heritage. The purpose of the research is the theoretical and methodological substantiation and development of practical mechanisms for the sustainable development of tourism and the hospitality sector, ensuring an effective balance between the economic interests of businesses and the requirements for protecting historical heritage and preserving the community’s cultural identity under transformational processes. One of the most effective tools for implementing this approach in managing historic environments is recognized as the street design code. In urban planning science, this concept refers to a regulatory and planning document that establishes a set of parameters for the architectural and spatial organization and visual identity of a specific area (street, block) with the aim of preserving historical and cultural heritage, improving the quality of the urban environment, and ensuring sustainable development.Thus, the design code acts not only as a set of aesthetic requirements but also as a mechanism for reconciling the interests of businesses, authorities, and the local community. It becomes particularly important to balance the requirements of the design code with the conditions of franchise networks, where businesses are often obliged to comply with strict franchisor standards for storefront design, corporate colors, and sign dimensions, which directly contradict the authentic historical style. This makes it possible to form a predictable regulatory environment for investment, ensure the preservation of heritage, and develop a competitive tourism product.
Keywords: tourism; hospitality sector; protection of historical heritage; street design code; franchise